A Review of Epidemiology, Clinical Manifestations, and Therapeutic Approaches for Monkeypox: Review Article (Journal of Pharma Insights and Research, 2024)
Monkeypox, a zoonotic disease caused by the monkeypox virus belonging to the Orthopoxvirus genus, has emerged as a significant public health concern worldwide. Initially confined to endemic regions in Central and West Africa, the disease has spread globally, affecting multiple countries across continents. The virus primarily transmits through close contact with infected animals, humans, or contaminated materials. Clinical presentations range from mild symptoms to severe complications, with characteristic features including fever, lymphadenopathy, and distinctive skin lesions progressing through various stages. Recent outbreaks have demonstrated altered transmission patterns and clinical manifestations, particularly affecting specific population groups. Diagnostic approaches encompass molecular techniques, serological testing, and clinical assessment. While supportive care remains the primary management strategy, antiviral medications like tecovirimat show promise in severe cases. Vaccination strategies, including both pre-and post-exposure prophylaxis, play crucial roles in prevention and outbreak control. Public health measures, surveillance systems, and international collaboration are essential components in managing the spread of monkeypox. The emergence of monkeypox as a global health challenge necessitates continued vigilance, enhanced preparedness, and coordinated response efforts to effectively contain and manage future outbreaks.